2006
DOI: 10.2514/1.17547
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Ramjet-Mode Combustion in a Dual-Mode Scramjet Engine

Abstract: Downstream combustion ramjet-mode operation in a dual-mode engine combustor was studied experimentally with a Mach 2.5 wind tunnel. In this downstream combustion ramjet mode, subsonic combustion was attained in the downstream straight-duct section without a geometrical throat. The experimental results are presented. The total temperature and the total pressure in the vitiation air heater were 800 K and 1.0 MPa, respectively. Pitot pressure and gas sampling were measured on the exit plane of the combustion mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Authors demonstrated the advantages of the downstream combustion ramjet-mode with the dual-mode scramjet engine combustor model [9][10][11] . The advantages of the downstream combustion ramjet-mode were summarized as follows:…”
Section: Downstream Combustion Ramjet-modementioning
confidence: 99%
See 1 more Smart Citation
“…Authors demonstrated the advantages of the downstream combustion ramjet-mode with the dual-mode scramjet engine combustor model [9][10][11] . The advantages of the downstream combustion ramjet-mode were summarized as follows:…”
Section: Downstream Combustion Ramjet-modementioning
confidence: 99%
“…Authors investigated the downstream combustion ramjet-mode in a scramjet engine combustor [9][10][11] . In the downstream combustion ramjet-mode, the subsonic combustion was attained in the downstream divergent duct.…”
Section: Introductionmentioning
confidence: 99%
“…22 In the dual-mode engine, an isolator is installed between the inlet and the combustor to isolate high pressure in the combustor from the inlet. Supersonic airflow from the inlet is decelerated to subsonic velocity through the pseudo-shock in the isolator in the ramjet mode.…”
Section: E Dual-mode Combustormentioning
confidence: 99%
“…When the step is in the pseudo-shock, a ratio of pressure at the step to that at exit of the pseudoshock is almost unity, differing from the ratio of Eq. (22) in which the step is located upstream of the pseudo-shock. (23) Then, the frictions are related as follows, differing from the relation expressed in Eq.…”
Section: B Effect Of Backward-facing Step On Startingmentioning
confidence: 99%
“…[7][8][9] When a scramjet engine is operated in ramjet mode, supersonic flow is decelerated to subsonic speed through a pseudo shock wave within the isolator, and the subsonic flow is re-accelerated to supersonic speed due to heat release by combustion. Although this conventional ramjet-mode operation assumes fuel injection within the constant-area combustor, Kanda et al 7) and Kato et al 8) attempted fuel injection at the exit of the diverging combustor to form the choking point there in their scramjet component tests. This downstream combustion ramjet-mode operation resulted in a lower peak pressure than in conventional ramjetmode operation without deterioration of thrust performance.…”
Section: Ramjet-mode Operation With Downstream Combustion In a Scramjmentioning
confidence: 99%